Educação ambiental na Floresta Nacional do Tapajós: uma abordagem como cientista ambiental do lugar de onde veio - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
This paper looks at Environmental Education (EE) in the Tapajós National Forest (FLONA) from the perspective of a resident and environmental scientist from the place where he lived. The aim is to investigate the phenomenon of environmental education in the Tapajós National Forest by mapping environmental education actions between January 2019 and June 2024. Adopting a qualitative-quantitative approach, the research seeks a more comprehensive and in-depth understanding of the phenomenon in question. It was conducted through interviews with an official from the Chico Mendes Biodiversity Institute (ICMBio), complemented by the organization and analysis of secondary institutional data requested from the management body of the conservation unit. The results of the survey indicate that only seven environmental education activities have been carried out in the last five years. The Tapajós National Forest is home to a total of 23 communities and three indigenous villages, but only five communities and one indigenous village took part in these initiatives. The themes addressed reflect contemporary and urgent concerns, such as the climate and water crisis, as well as the inclusion of topics such as the conscious use of fire and recycling. However, the management of the activities faces significant challenges, such as the lack of trained staff to carry out the actions, the low financial investment directed towards environmental education and the difficulties in monitoring these initiatives. Therefore, this study aims to contribute to the discussion on the management of environmental education activities in the Tapajós FLONA through analyzed data and the study of a resident environmental scientist in the region.
Keywords: Educação Ambiental; FLONA; Amazônia; CNPQ:: CIENCIAS AMBIENTAIS